Correlation Analysis of Expression Profile and Quantitative iTRAQ-LC-MS/MS Proteomics Reveals Resistance Mechanism Against TuMV in Chinese Cabbage (Brassica rapa ssp. pekinensis) - Lyu, Shanwu; Gao, Liwei; Zhang, Rujia; Zhang, Changwei; Hou, Xilin (Frontiers in Genetics, 2020)
The arms race between plants and viruses never ceases. Chinese cabbage, an important type of Brassica vegetable crop, is vulnerable to plant virus infection, especially to Turnip mosaic virus (TuMV). To better examine the molecular mechanisms behind the virus infection, we conducted a correlation analysis of RNA-Seq and quantitative iTRAQ-LC-MS/MS in TuMV-infected and healthy Chinese cabbage leaves. There were 757 differentially expressed genes and 75 differentially expressed proteins that were screened in Chinese cabbage plants infected with TuMV. These genes were enriched in many pathways, and among them, the plant hormone signal transduction, plant-pathogen interaction, and protein processing in the endoplasmic reticulum pathways were suggested to be closely related pathways. A correlation analysis between RNA-Seq and quantitative iTRAQ-LC-MS/MS was then further explored. Finally, we obtained a preliminary network of several candidate genes associated with TuMV infection, and we found that they mainly belonged to calcium signaling pathways, heat shock proteins, WRKY transcription factors, and non-specific lipid transfer proteins. These results may lead to a better understanding of antiviral mechanisms and of disease-resistant breeding.